Appendix 3.8: Senate Bill 2593, “An Act Creating a Hydrogen Research and Development Center and Providing Funds Therefor, and for Other Purposes,” 15 November 2010 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Of the bills filed by Senator Ferdinand “Bongbong” Marcos Jr., this is one that best recalls his ties to his mother. According to Ben D. Kritz, in an article titled “Did Businessweek Fall for a 30-year-old Hoax?” published in The Manila Times on 28 October 2013, Imelda Marcos was told in the 1970s that the Philippines has vast deuterium deposits in the Philippine Trench, and has since been spending “‘millions of dollars a year’ to secure an exclusive right to extract water from the trench.” Kritz (2013) thereafter cites a study that showed that “[shallower] waters...actually have a slightly higher amount of deuterium” than undersea trenches, and that the former dean of the UP College of Science and nuclear physicist Roger Posadas, once “offered a scathing assessment of the country’s enthusiasm for the potential of deuterium” in a 1988 article published in The Manila Standard Today , “saying that the whole yarn was ‘a gauge of our country’s extremely unscientific culture and strong proclivity toward reliance on miracles as solutions to our national problems.’” Bongbong Marcos’s bill states the myth that the Philippines has the world’s biggest deuterium deposits not only in its explanatory note, but also in the bill’s declaration of policy (“hydrogen has been proven to be most abundant in the country”).